O comportamento dos gastos em saúde e educação em relação à receita tributária dos municípios de Minas Gerais - Pereira, Carlos Antônio (2023)
Faced with social failures in the market, the State, with the power of defense, seeks to promote equity and social justice, not only with a coherent collection, but with the use of efficiency in the allocation of resources. In view of these facts, this thesis aims to analyze, among the municipalities of Minas Gerais, the behavior of spending on education and health, as a government allocation function, according to the Theory of Public Finance, in relation to collection, either itself or arising from current transfers – distributive budgetary function. It was also verified how the collected resources and the expenses with health and education help in the development of the municipalities. For the formation of the sample, the 853 municipalities of Minas Gerais were considered, in the period from 2018 to 2020, and the data were collected on the website of the Court of Auditors of the State of Minas Gerais, as well as the Brazilian Institute of Geography and Statistics and Firjan. The set of variables was explored from the descriptive analysis with the evidence of considerable heterogeneity between municipalities and between different geographic regions. The variables of collection and expenditure on health are increasing, both in average per capita values and in percentages of current revenue, while expenditure on education has been decreasing. Although the variables showed significant correlations, they did not show normal distribution, including about residuals. Expenditures on primary education showed higher correlations with transfer flows, while children's education showed a greater transfer force with its own collection. In this sense, for the health area, hospital care showed greater collaboration with its own collection, while primary care was more correlated with current transfers. With the use of the collection variable, the municipalities were grouped into clusters and identified their characteristics. By means of logistic regression, it was possible to describe the behavior between the municipal development of Minas Gerais related to variables of collection and expenditure on health and education. The research results showed that, although expenditures on health and education are exclusive and rivals in the budget, the explanatory power of the regression model increases when analyzed together.